Juror Questions During Trial: A Window into Juror Thinking - Diamond, Shari Seidman (2006)
The jury has undergone a dramatic transformation from its earliest incarnation when jurors acted as witnesses, investigators, and tribunal. In the modern American jury trial, the parties determine what jurors learn during the proceedings. Jurors of today, assigned the role of audience members until deliberations begin, typically speak in the courtroom only during jury selection and through their verdict at the end of the trial. In light of their enforced silence throughout the trial, jurors have no opportunity to clarify or check on their interpretation of the evidence and they provide few external indications about their thinking as the trial unfolds. Although post- trial juror interviews and jury simulations contribute to our understanding of how jurors react to evidence, these indirect sources are not the on-line reactions of jurors during trial. The modern veil on juror participation that conceals juror thinking during trial, however, is being lifted partially in a small, but increasing, number of American courtrooms. In these courtrooms, jurors are permitted to submit questions for witnesses during trial. The questions that the jurors submit provide a unique window into juror thinking during the trial